Childcare as Infrastructure: The Impact of COVID-19 on Childcare and Gender Equity - Alicia Sasser Modestino; Zachary Finn; Jamie Ladge; Alisa Lincoln (Institute of Labor Economics (IZA), 2025)
Conducting a nationally representative survey of 2,500 working parents between Mother's and Father's Day of 2020, we examine gender differences in the childcare shock during the COVID-19 pandemic. Drawing on demographic, household, and labor market factors, we document gender differences in time use, work status, mental health, job satisfaction, and employer benefits. Using variation in pre-pandemic characteristics to measure exposure to the childcare shock, we find mothers in the more vulnerable group were 15 percentage points more likely to experience a reduction in hours due to childcare than similarly situated fathers. Although paid family leave helped narrow the gap in hours between mothers and fathers in the affected group, newer COVID-19 workplace practices such as working from home and childcare subsidies had no effect.
Keywords: D13; D91; I30; J22; J28; J71; 330; household decision-making; gender differences; childcare; paid leave; COVID-19